2016
DOI: 10.24033/bsmf.2725
|View full text |Cite
|
Sign up to set email alerts
|

Gradings on Lie algebras, systolic growth, and cohopfian properties of nilpotent groups

Abstract: We study the existence of various types of gradings on Lie algebras, such as Carnot gradings or gradings in positive integers, and prove that the existence of such gradings is invariant under extensions of scalars.As an application, we prove that if Γ is a finitely generated nilpotent group, its systolic growth is asymptotically equivalent to its word growth if and only if the Malcev completion of Γ is Carnot.We also characterize when Γ is non-cohopfian, in terms of the existence of a non-trivial grading in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…As we shall see in Proposition 9.3, the above theorem generalizes a recent result of Cornulier (Theorem 3.14 from [13]).…”
Section: 7supporting
confidence: 79%
See 2 more Smart Citations
“…As we shall see in Proposition 9.3, the above theorem generalizes a recent result of Cornulier (Theorem 3.14 from [13]).…”
Section: 7supporting
confidence: 79%
“…A classical example is the unipotent group U n (Z), which is known to be filtered-formal by Lambe and Priddy [42], but not graded-formal for n ≥ 3. In [13], Cornulier showed that the filtered-formality of a finite-dimensional nilpotent Lie algebra is independent of the ground field, thereby answering a question of Johnson [37]. The much more general Theorem 1.1 allows us to recover this result in Proposition 9.3.…”
Section: 5mentioning
confidence: 92%
See 1 more Smart Citation
“…For example, Belegradek considered in [8] when such a lattice must be co-Hopfian, and in particular when they are not. Non co-Hopfian subgroups of nilpotent Lie groups were also studied by Dekimpe, Lee and Potyagailo in [22,23,24], and by Cornulier in [20]. Here is a general version of Problem 8.1:…”
Section: Coverings Of the Klein Bottlementioning
confidence: 97%
“…As a consequence of this theorem we construct a nilmanifold admitting an Anosov diffeomorphism but no expanding map in the last section. Some of these results were proved independently and by different methods in [2] by Y. Cornulier. More detailed references to the work of Y. Cornulier are given throughout paper.…”
mentioning
confidence: 94%